Scrap Gold Recovery: Recycling, Fabrication and Electrochemical Characterization of Low-Cost Gold Electrode - Al Mamun, Mohammad; Abdul Wahab, Yasmin; Hossain , M. A. Motalib; Abu Hashem; Johan , Mohd Rafie (Malaysian Catalysis-An International Journal, 2022)
As a noble metal, gold is considered the most popular material in electrocatalysis. In spite of that, this metal is a highly expensive material in the manufacture of low-cost appliances. In the present work, scrap gold, produced in jewellery as waste, is introduced as a low-cost resource of gold to be recycled. A gold electrode was fabricated by connecting the tablet shaped recycled gold with copper wire inserting into a polytetrafluoroethylene (PTFE) tube. The manufactured electrodes are easily renewable, modifiable with nanomaterials and show excellent electrochemical characteristics in presence of redox species. The CV (cyclic voltammetry), DPV (differential pulse voltammetry), and EIS (electrochemical impedance spectroscopic) analysis data also infer that the developed recycled gold-based electrodes would be suitable for the development of low-cost electrocatalytic sensors devices.